2019
DOI: 10.1186/s12913-019-4683-z
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ experiences of providing care for women survivors of sexual violence in psychiatric inpatient units

Abstract: BackgroundSurvivors of sexual violence, who are predominantly women, commonly access mental health services. Psychiatric inpatient units in Australia are predominately mixed gender and may further retraumatise these women. Sexual violence is under-recognised by mental health professionals and there is a lack of adequate policy or direction for mental health service services. To date, only a small amount of research has focused on health professionals’ experiences of providing trauma-informed care to women in p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…That administrator will usually get no supervision or recognition for the emotional element of their work. In studies where the participants were professionals working in diverse environments (e.g., acute ward, prison, domestic violence shelter, police) (Javaid, 2017;Kreinath, 2019;Newman et al, 2019;O'Dwyer et al, 2019), there is an added level of complexity. It is even more difficult to ascertain the traumatic effects of working with this population from the effects of the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That administrator will usually get no supervision or recognition for the emotional element of their work. In studies where the participants were professionals working in diverse environments (e.g., acute ward, prison, domestic violence shelter, police) (Javaid, 2017;Kreinath, 2019;Newman et al, 2019;O'Dwyer et al, 2019), there is an added level of complexity. It is even more difficult to ascertain the traumatic effects of working with this population from the effects of the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…They often faced ethical and professional dilemmas about their role and the usefulness or necessity of their role (Backe, 2018;Javaid, 2017). Faced with these issues, staff felt stressed and unable to cope with the demands of the job, their sense of selfworth, confidence, and self-efficacy as professionals were diminished, felt disempowered and meaningless in their job, as well as experiencing constant doubt and ruminations over decisions taken due to no longer perceiving themselves as skilled to a high standard (Albaek et al, 2020;Brend et al, 2020;Gatuguta et al, 2019;O'Dwyer et al, 2019). This effect was exacerbated when they lacked clear guidance, guidelines, or resources (Backe, 2018;Kreinath, 2019), when there was an overreliance on procedures, and when they did not feel that the organizations they worked for would support their decisions (Albaek et al, 2020).…”
Section: Effects Of Working With Victim-survivors Of Sexual Violence On Professionals' Well-beingmentioning
confidence: 99%
“…Dar mažiau dėmesio skiriama profesionaliam darbui su smurtautojais, todėl galėtų būti vykdomos mokymo programos specialistams, kurios suteiktų įgūdžių, kaip įtarti seksualinę prievartą bei kuo greičiau pagelbėti aukai. Programų tikslas -pristatyti galimas seksualinio smurto apraiškas, priežastis bei sprendimo būdus [36]. Svarbu skatinti ir aukas kuo anksčiau prisipažinti apie patiriamą lytinę prievartą ir nebijoti visuomenės kritikos.…”
Section: Tyrimo Rezultatai Ir Jų Aptarimasunclassified
“…Commonly, professionals do not ask about a possible history of violence due to inadequate knowledge, confidence, and skills to respond to such confessions (Rose et al, 2011;Hepworth and McGowan, 2013;Nyame et al, 2013). Moreover, there is no recommended action for mental health services and clinical care to follow up on when a woman has experienced sexual violence (O'Dwyer et al, 2019). In addition, prior research revealed that secondary traumatic stress symptoms are common among professionals who work with traumatized patients (O'Halloran and Linton, 2000;Canfield, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification of these dyads and the development of a secure attachment should be a focus in early interventions. Prior research has shown that experienced violence in general is under-recognized by mental health professionals ( O’Dwyer et al, 2019 ). Commonly, professionals do not ask about a possible history of violence due to inadequate knowledge, confidence, and skills to respond to such confessions ( Rose et al, 2011 ; Hepworth and McGowan, 2013 ; Nyame et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%